PENGARUH METODE RESITASI MENGGUNAKAN MEDIA MIND MAPPING TERHADAP KEMAMPUAN MENULIS PENGUMUMAN PADA SISWA KELAS 5 SEKOLAH DASAR - apriliya, pratiwi; Andjariani, Endang Wahju; Budhi Rahayu Sri Wulan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the resitation method using mind mapping media on the ability to write announcements in class V elementary school announcement material. This research was conducted because of the lack of ability of students in making announcements in accordance with the procedure, resulting in students not being able to achieve the KKTP (criteria for achieving learning objectives) that has been determined with a score of 75 according to the provisions. The type of research used is quantitative using pre- experimental with one group pretest- posttest. The data collection technique in this study was a writing skill test and student activity observation results. The results of the research on this data begin with the validation of the questions carried out using spss and get a score on each question <0.05 then H0 is accepted and declared valid, then the reliability test gets the results 0.897> 0.07 then declared reliable, and the data normality test gets the p-value 0.200> 0.05 then H0 is accepted so that the residuals are normally distributed, the last homogeneity test gets p-value 0.934> 0.05 then H0 is accepted so that the residuals are homogeneous. The results of the effect of the resitation method on students' announcement writing ability reached 0.004 <0.05 so that H0 was rejected in the simple linear regression hypothesis test, meaning that there was an influence in the implementation of learning. The results of the observation of student activities got an average of 20.09 obtained from the Likert scale, while the results of the ability to write student announcements reached 73% with a high category obtained from N-Gain based on spss calculations and showed an increase which previously only obtained 30% or 6 students in a total of 22 students in class V, so this method can be used to improve the ability to write announcements in grade V elementary school students.